2021
DOI: 10.1177/03635465211057117
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Autologous Osteochondral Transplantation With and Without Extracellular Matrix Cartilage Allograft Augmentation for Osteochondral Lesions of the Talus

Abstract: Background: Autologous osteochondral transplantation (AOT) using a cylindrical graft in the treatment of osteochondral lesions of the talus (OLTs) is typically indicated for patients with larger lesions. However, with lesions that are irregular in shape, the AOT graft may not completely replace the lesion. For these lesions, we utilize extracellular matrix cartilage allograft (EMCA) augmentation in AOT to act as a physiologic grout at the host-graft interface. Purpose: To determine if the combination of EMCA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“… f Multiple studies: 15,36,39,47,48,50,60,68,70,71,74,75,83,84,87 -90,95 -97,100,105,106,108,110,120,126,128,129,132,136,138,148,151,152,154,156,159 -161,163,171 -175,178,184,188,191,193,194,197,203 . …”
Section: Resultsmentioning
confidence: 99%
“… f Multiple studies: 15,36,39,47,48,50,60,68,70,71,74,75,83,84,87 -90,95 -97,100,105,106,108,110,120,126,128,129,132,136,138,148,151,152,154,156,159 -161,163,171 -175,178,184,188,191,193,194,197,203 . …”
Section: Resultsmentioning
confidence: 99%
“…15 However, few studies paid attention to the depth of the subchondral lesion with small cysts presented. Traditional concepts suggest not to treat cystic lesions with microfracture 3,23 ; however, it is difficult to justify the use of osteochondral or osteoperiosteal transplantation for small cystic lesions. Jung et al 16,17 used microfracture to treat a group of cystic OLTs and reported promising clinical and radiographic outcomes based on pain and function scores and computed tomography scans.…”
Section: Discussionmentioning
confidence: 99%
“…The CBMA was truly biologically active, and the secretome produced was responsible not only for chondrogenic integration but was also chondroprotective of the surrounding cells. 17,18…”
Section: Concentrated Bone Marrow Aspiratementioning
confidence: 99%
“…The CBMA was truly biologically active, and the secretome produced was responsible not only for chondrogenic integration but was also chondroprotective of the surrounding cells. 17,18 Figure 1 A, Images identifying the anterior superior iliac crest, and a jamshidi needle is used to access the area between the inner and outer tables of the iliac crest. B, Heparin solution is within the syringe to prevent clotting.…”
Section: Concentrated Bone Marrow Aspiratementioning
confidence: 99%